ANALISIS KEPUASAN PENGGUNA TERHADAP DESAIN ANTARMUKA GRAFIS (GUI) PADA APLIKASI TIKTOK - Dina Padilah Padang; Raisya Aulia; Dwi Desnita Salsabila Nasution; Delima Yuni Sneva; M. Khalil Gibran (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines user satisfaction with the Graphical User Interface (GUI) design of the TikTok application. The rapid development of digital technology and the increasing use of social media demand an interface design that is comfortable and easy to use. This study aims to describe the level of user satisfaction and to identify GUI aspects that influence user experience, such as visual appearance, navigation, and system responsiveness, using a descriptive quantitative method through questionnaires. The results indicate that most users are satisfied with TikTok’s GUI design, particularly in terms of visual appeal and ease of feature access. However, frequent interface changes and the complexity of certain features remain challenges for some users. These findings emphasize that design consistency and ease of navigation are important factors in enhancing user experience; therefore, continuous evaluation of the interface is necessary.